Fattori Predittivi di Margini Chirurgici Positivi Dopo Chirurgia Conservativa per Neoplasia Renale: Analisi Retrospettiva Monocentrica su 298 Pazienti. Issue 1 (January 2014) - Schiavina, Riccardo; Borghesi, Marco; Chessa, Francesco; Rizzi, Simona; Martorana, Giuseppe
Predictors of positive surgical margins after nephron-sparing surgery for renal cell carcinoma: retrospective analysis on 298 consecutive patients: Objectives: Aim of our study was to evaluate the predictive factors of positive surgical margins (PSM) in a cohort of patients who underwent partial nephrectomy (PN) for renal cell carcinoma. Material and Methods: We retrospectively evaluated our Institutional database of patients treated with open or laparoscopic PN between 200 and 2013. Categorical variables were compared using Pearson's chi-square test and linear-by-linear association. Multivariable Cox analysis was used in order to evaluate independent predictors of PSM. Results: Surgical margins were found to be negative in 274 out of 298 patients (91.9%), and the remaining 24 (8.1%) patients had PSM at the final pathological exam. The median clinical size was significantly lower in patients with PSM than those with negative margins (2.6 vs. 3 cm, p=0.03). At univariable analysis, a shorter operative time (p=0.04), a malignant histotype (p=0.04) and higher Fuhrman grade (p=0.02) were observed in patients with positive surgical margins compared to those without PSM. At multivariable analysis, median tumor dimension (p=0.02), the malignant histotype (p=0.01) and the high Fuhrman grade (3-4) (p=0.01) were found to be independent predictive factors of PSM. Conclusions: The most important goal of any PN is to reach negative surgical margins. In our study, clinical tumor dimensions, malignant tumor histotype and the high Fuhrman grade demonstrated to be independent predictive factors of PSM after nephron sparing surgery for renal cell carcinoma. Other prospective, multi-institutional studies are needed in order to confirm these results.